Strategi Pemasaran Usaha Mikro, Kecil, dan Menengah (UMKM) di Masyarakat Desa Sungai Mahang - Taufik, Hendra; Syam, Atalariq Faturrahman; Betranto, Agung Figo; Ichwansyah, Muhammad; Khairah, Hijratil; Putri, Marselina; Pratama, May Yunda; Aisyah, Siti; Hanfah, Zahra; Lestari, Ayu; Lelita, Vina (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This Real Work Lecture (KKN) activity aims to improve the marketing strategy of micro, small, and medium enterprises (MSMEs) in Sungai Mahang Village, with a focus on MSMEs located around the Jamiatun Muslimin Parid Tengah Mosque. This research was conducted through direct observation, interviews with MSMEs and consumers, as well as distributing questionnaires. The research results show that the majority of MSMEs in the village do not have an effective marketing strategy, which has an impact on low sales levels. Based on the results of the analysis, the KKN team provided training on digital marketing strategies, such as using social media and creating simple websites. Apart from that, the KKN team also helps MSMEs in designing more attractive product packaging. After implementing the program, there was an increase in MSME players' knowledge about the importance of marketing, and there were visible efforts to implement new marketing strategies. However, continued support is still needed from the village government and related institutions to ensure the sustainability of this program.